Implicações da gamificação no projeto de plataforma de educação on-line: um estudo de caso - Fabiana Bigao Silva (2018)
New ways of providing teaching and learning activities have been discussed from the current pervasiveness of information technologies, since they are able to make flexible some involved variables in learning environments as time, location and format. In this context, there are challenges about how to assign quality to learning activities and how to inspire students in their search for constructing knowledge. The gamification the use of game elements in environments and situations outside of games context has been considered a tool that contributes to higher levels of incentive in using learning systems within educationalscope. The literature exhibits good quality quantitative researches about the subject gamification in education, including behavior metrics. However, these metrics do not capture some facts, for example: the motivators for certain student behaviors, the emotions involvedin the learning experience, the view that the mechanism of gamification is considered more efficient than traditional ways of teaching, the students preferences and profiles. There are a few qualitative researches that could have verified subjective user experiences of the systems with gamification elements. Thus, the general goal of this thesis is to describe the implications of gamification to the design of online educational environments. In order to reach our goal, we created a model that organizes the project of an environment with gamification elements for online teaching and learning, based on the conceptual frameworkof a well-known initiative. The goals of the project were defined according to the participant profiles and their target-behaviors, as well as to the entertainment associated with each profile. The project was implemented in a platform of teaching, and a case study was carried out to find out the behaviors and subjective experiences of the participants interacting withelements of gamification in the platform. The results obtained from the connection among the log system, the evaluation of forms answered by participants and the exam of interviews have made possible the analysis in the case study. According to such analysis, the most important factors that promote the intrinsic motivation in the learning process are: journeyswith qualified contents and no need to catenate contents, the explanation of errors, and the possibility of new tentative. The awards by performance, which furnish sense of competency, are real incentives to the extrinsic motivation and should be considered in the balance between the two kinds of motivation within the gamification environment. The social panel(ranking), which provides comparison among students, is also a valuable mechanism, insofar as it can foster both intrinsic and extrinsic motivation.